1997
DOI: 10.1002/mrm.1910380517
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function in infarcted and remote regions early after infarction in man: Assessment by magnetic resonance tagging and strain analysis

Abstract: Early after infarction in the perfusion bed of the left anterior descending coronary artery, cine MRI with spatial modulation of magnetization (SPAMM) tagging (7-mm grid) was used for short- and long-axis cardiac imaging. Two-dimensional strain analysis of triangular finite elements was performed between end-diastole and end-systole. Patients (n = 10) were compared with age-matched healthy subjects (n = 8). The anteroseptal region at midventricular level was considered representative for "infarcted" and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…22 In humans, it has also previously been shown that regional blood flow in the remote zone is increased in infarcted hearts 23 and that those regions exhibit hyperfunction compared with controls. 23,24 Similarly, we found that the pattern of work done by the infarcted hearts was prominently different than in control hearts. cRMW L in the lateral wall (coincident with the infarcted region) was eliminated, and septal cRMW L was increased.…”
Section: Regional Workmentioning
confidence: 55%
“…22 In humans, it has also previously been shown that regional blood flow in the remote zone is increased in infarcted hearts 23 and that those regions exhibit hyperfunction compared with controls. 23,24 Similarly, we found that the pattern of work done by the infarcted hearts was prominently different than in control hearts. cRMW L in the lateral wall (coincident with the infarcted region) was eliminated, and septal cRMW L was increased.…”
Section: Regional Workmentioning
confidence: 55%
“…Depolarization is followed by contraction of the myofibers. The normal contraction pattern of the left ventricle ͑LV͒ may be affected by underperfusion 2,15,25,52 and abnormal conduction of the depolarization wave. 34,53 With the rapid evolution of methods to determine myocardial deformation non-invasively, deduction of pathology from such measurements is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 2(a) shows the first principal strain maps for visual comparisons, as there is a strong inverse relation between the first principal strain and the extent of myocardial infarction [9]. There is almost no deformation in the infarcted regions in the ground truth.…”
Section: Synthetic Datamentioning
confidence: 99%